Modeling digital interactive TV users behavior - Basilio, Samuel da Costa Alves; Moreno, Marcelo Ferreira; Barrére, Eduardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
System performance appraisal needed at the development of new large scale distributed systems are faced with the challenge of correct estimated load that is imposed on them. When dealing with Digital Tv, including terrestrial, cable, satellite and IPTV obtaining such load characterization from real deployment scenarios has proved very difficult, due to the impediment of experimental access to these operational broadcast networks. Thus, the researcher usually uses simulations that impose grossly approximate workloads, oversized or fictitious to his system, bringing uncertainty to potential service providers as to optimized design of the necessary equipment. We present at this paper a mathematical model of simple implementation, able to represent the behavior of users of Digital TV. The model can be parameterized to represent different behavior states of the simulated system and thus adapt to various interest scenarios.